ANALYSIS OF THE EFFECT OF E-FILING AND E-BILLING ELECTRONIC MEDIA SYSTEM QUALITY ON TAXPAYER SATISFICATION (STUDY OF TAXPAYERS AT KPP PRATAMA PEKANBARU TAMPAN) - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
The puspose of this study is to determine and analyze the effect of the Quality of Electronic Media Systems e-filing and e-billing on taxpayer satisfaction (study of taxpayers at KPP Pratama Pekanbaru Tampan). Determination of the sample in this study using purposive random sampling. Where the sampling criteria in this study are individual taxpayers who have used the e-system. The data analysis method used is multiple linear regression analysis using the help of the SPSS version 21 program. The independent variables in this study are the Quality of the e-Filing System and the Quality of the e-Billing System, while the dependent variable is Taxpayer Satisfaction. The results showed that partially the quality of the e-filing media system did not have a significant effect on the level of taxpayer user satisfaction. Meanwhile, the quality of the e-billing media system has a significant positive effect on the level of taxpayer user satisfaction.